PENGEMBANGAN MEDIA FLASHCARD BERBASIS METODE SILABA DALAM MEMBACA PERMULAAN KELAS I SEKOLAH DASAR - Rahmah Rivandani Ihsanah; Veryliana Purnamasari; Lina Putriyanti (STKIP Subang, 2023)
The implementation of less varied learning media leads to failure in achieving specific learning objectives, especially in early reading. Hence, there's a need for effective new developments or innovations in creating learning media. The objective of this research is to produce silaba-based flashcard learning media for early reading in first-grade elementary school that are valid and practical. The research method used is Research and Development (R&D), employing the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The developed learning media consists of flashcards based on the syllable method, created using the Canva application. This study involves media experts, content experts, and teachers to validate the suitability and practicality of the media. Instruments used in this research include observation, interviews, and response questionnaires. Expert assessments were calculated using Likert and Guttman scales. The research results indicate that silaba-based flashcards show an average expert media questionnaire result of 95.5%, an expert content questionnaire result of 93.33%, a teacher response questionnaire result of 95%, and a student response questionnaire result of 91.05%. This demonstrates that silaba-based flashcards for early reading in first-grade elementary school are both practical and valid for use in SDN 01 Kemuning-Pemalang.